Digital Privacy and Netizens’ Reactions to Obscene Videos: Perspectives from Cyberpsychology and Law - Ulfa Dyah Mustika; Galih Setyo Refangga; Sri Wiworo Retno; Sigit Budi Santoso (Fakultas Psikologi Universitas Yudharta Pasuruan, 2026)
This study aims to analyze netizens’ responses to a case involving an indecent video featuring a teacher from a cyberpsychology perspective and to examine the associated criminal law implications. The study employed a descriptive qualitative approach, utilizing data collection techniques such as digital observation, unstructured interviews, and documentation. The study’s informants consisted of ten individuals selected through purposive sampling based on their involvement in accessing, following, or responding to information related to the case under investigation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and drawing conclusions. The results indicate that netizens’ responses are not homogeneous but encompass empathetic responses, victim-blaming, passive consumption, and content-saving practices. Although most informants understood the importance of digital privacy, this understanding is not always accompanied by behavior that supports privacy protection. This study also found a gap between normative legal awareness and understanding of the legal protection mechanisms available to victims. Furthermore, netizens’ involvement occurs not only through the act of sharing information but also through activities such as accessing, saving, and following case developments, which contribute to the continued exposure of victims in the digital space.